(untitled) (Prostor, 2025)
The first generation of modern stadiums was constructed during the early urbanization process of the Republic of Turkey, particularly with the contributions of Italian architect Paolo Vietti-Violi. These stadiums transformed both the physical environment and social identity, serving as some of the earliest examples of modern architecture. Accordingly, the first generation stadiums from the early Republican era were designed using modern architectural principles and spatial representations of Republican ideology, aiming to cultivate a modern, secular, and healthy society. In this sense, the study aims to reveal the effects of design decisions on the physical quality of space and the ways these spaces have transformed into tools for building a modern nation by examining the historical context, architectural components, and social impacts of the stadiums in question together. The study method involved an in-depth evaluation of all historical sources and materials to find out how the first generation of stadiums developed and shed light on socio-political influences. The study will reveal the aesthetic ideals of the time, focusing on design elements, materials, and the spatial organisation of the stadiums, as well as their social and cultural impact in producing a modern, secular, and healthy nation.